(untitled) (Ustozlar uchun, 2025)
Abstract: This paper explores the major challenges and opportunities faced by learners of English as a foreign language (EFL). It discusses linguistic, psychological, and cultural barriers, as well as the growing opportunities provided by globalization and digital technology. The study is based on qualitative research through classroom observation and learner interviews. Findings show that although EFL learners face difficulties related to pronunciation, motivation, and limited exposure, technology, intercultural communication, and modern teaching approaches can significantly enhance their learning outcomes.